2009
DOI: 10.1002/jmv.21466
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic spread of hepatitis C virus genotype 3a and relation to high incidence of hepatocellular carcinoma in Pakistan

Abstract: Studies conducted in different populations worldwide revealed an association between HCV genotype 1 and the development of hepatocellular carcinoma (HCC) than in infection with other HCV genotypes. There are reports which reveal the association of HCV genotype 3a (HCV-3a) with hepatic steatosis and fibrosis but its relation with the development of HCC has not been investigated. In Pakistan, where the incidence of HCC is increasing, 189 patients with chronic liver disease including 82 with HCC were enrolled. HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 45 publications
(58 reference statements)
4
33
1
2
Order By: Relevance
“…As short sequences can adversely affect the calculation of important parameters in MCMC analyses, they were not included in this analysis. The evolutionary rate of the Gt3a sequences from the global data set was 1.65 Ï« 10 ÏȘ3 s/s/y which is slightly higher than previously noted (1.3 Ï« 10 ÏȘ3 s/s/y [20] [22]), but another study has estimated that extant global Gt3a sequences coalesced much earlier, approximately 300 years ago (20). In the latter study, however, three sequences from Pakistan formed a distinct cluster which was phylogenetically distant from the remainder of the Pakistani sequences and sequences from other countries; without this outlying cluster, the remaining global Gt3a pool coalesces approximately 80 years ago, supporting our findings.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…As short sequences can adversely affect the calculation of important parameters in MCMC analyses, they were not included in this analysis. The evolutionary rate of the Gt3a sequences from the global data set was 1.65 Ï« 10 ÏȘ3 s/s/y which is slightly higher than previously noted (1.3 Ï« 10 ÏȘ3 s/s/y [20] [22]), but another study has estimated that extant global Gt3a sequences coalesced much earlier, approximately 300 years ago (20). In the latter study, however, three sequences from Pakistan formed a distinct cluster which was phylogenetically distant from the remainder of the Pakistani sequences and sequences from other countries; without this outlying cluster, the remaining global Gt3a pool coalesces approximately 80 years ago, supporting our findings.…”
Section: Discussioncontrasting
confidence: 58%
“…The second peak of Gt3a lineage expansion (1951 to 1975) suggests that migration from the Indian subcontinent may be the source of currently circulating Gt3a sequences in Scotland. Approximately 1% of the Scottish population originates from Pakistan, where epidemic Gt3a transmission has been shown to have occurred earlier than in any other country (22). Extant Gt3a strains in the United Kingdom are considered to originate from the Indian subcontinent where HCV is endemic (23) via migration which peaked in the 1950s and 1960s, and subsequently, these sequences pro-…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes 1, 2 and 3 are distributed worldwide and contribute to the majority of HCV infection. Subtypes 1a and 1b are most common in Europe, the USA and Japan, and subtypes 2a and 2b are predominant in Japan, North America and Europe, while subtype 3a is most prevalent in the Indian subcontinent and Thailand [11,12,13]. On the other hand, the less common genotypes 4, 5 and 6 are restricted to certain geographic areas.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the initial spread time of HCV infection is associated with the prevailing socioeconomic conditions, reflecting the present incidence as well as predicting the future development of HCC [11,27,28,29,30]. Because HCC is associated directly with the incubation period of HCV infection and HCV subtype 3a is the predominant genotype [11,30], the initial spread of HCV subtype 3a among the Thai population may occur later than in other countries. …”
Section: Introductionmentioning
confidence: 99%
“…Portanto, o rastreamento da transmissĂŁo Ă© fundamental para o controle do VHC e da Hepatite C (Khudyakov, 2012). A histĂłria da epidemia de Hepatite C Ă© muito dinĂąmica e em meados do sĂ©culo passado, houve um rĂĄpido aumento no nĂșmero total de infecçÔes, sendo os subtipos 1a e 1b prevalentes mundialmente (Magiorkinis GE, et al, 2009;Iles JC, et al, 2013), o genĂłtipo 2 e o subtipo 5a encontrados na África (Tanaka Y, et al 2006;Markov PV, et al 2009) e subtipo 3a localizado no PaquistĂŁo e Ásia Central (Tanaka Y, et al 2006;Khan A, et al 2009). Posteriormente, durante a dĂ©cada de 1980 e inĂ­cio de 1990, observou-se um rĂĄpido declĂ­nio no nĂșmero casos de Hepatite C aguda nos EUA (Williams LT, et al 2011).…”
Section: Epidemiologiaunclassified